ЗМІСТ ГОСПОДАРСЬКОЇ КОМПЕТЕНЦІЇ ДЕРЖАВНИХ ПІДПРИЄМСТВ - Zakharchenko, A.M.; Lubimov, I.M. (Економіка та право, 2009)
The article investigates provisions of the legislation that defines economic jurisdiction of state-owned enterprises. The proposals are grounded to specify economic jurisdiction of state-owned enterprises and work out the classification of rights and duties of such enterprises on the basis of specific features of their jurisdiction defined.